UNINTENDED BENEFITS OF MILLENNIUM DEVELOPMENT GOALS TO A CULTURALLY EMBEDDED RURAL ECONOMY - S. O. Olubiyo; A. E. Obayelu; A. Oriade (European Scientific Journal, ESJ, 2015)
The burden of local traditions to free people from the vagaries of poverty and economic doldrums in rural areas cannot be overemphasised. Traditional practices succinctly formed the premix of behaviour that exerts influence on decision making process on average rural entrepreneurs on many issues that borders on their means of livelihood. There is nothing untoward about reliance on traditions in decision making except it hinders independent thinking, savages enterprising behaviour and retrogresses or dampens enthusiasm to recognise and embrace ideas that have the potentials to improve quality of life and wellbeing. These phenomena are symptoms of adherence to culture and traditions that are common occurrence in rural societies. The successful governments have failed to accede to the yearning of the people instead they turned them to object of political games until the advent of the United Nation declarations that enforced a change in the game plan to address the seemingly problems of poverty ravaging the world. This paper therefore highlights the cultural and traditional web that impinged on rural entrepreneurs and the changes the millennium development goals (MDGs) have brought to governance and the potentials to rejuvenate rural economy.